A comparative study of chemical composition, phenolic compound profile and antioxidant activity of wild grown, field and greenhouse cultivated Physalis (P. alkekengi and P. peruviana) - Parisa Yari; Abolfazl Alirezalu; Soghra Khalili (Food Production, Processing and Nutrition)
Abstract Phytochemical properties and antioxidant activity of medicinal Physalis alkekengi fruit (wild and cultivated genotypes) and P. peruviana commercial species, were investigated (ten samples). Ripe fruits of P. alkekengi in comparison to P. peruviana, which is already regarded as an extremely functional fruit, possessed higher values of phytochemicals as well as antioxidant activity. In this present study, greatest phenolics content and antioxidant activity was observed in cultivated Physalis. The uppermost antioxidant activity was obtained in the fruit extract of cultivated P.alkekengi in C5 (Silvana) with 44.13% by DPPH method and C8 (Urmia) with 0.40 μM Fe++ g −1 FW by FRAP assay. Extracts obtained C8 and C4 (Khoy) possessed the highest total phenolic (34.12 mg GAE g−1 FW) and total flavonoid (7.06 mg QUE g−1 FW) contents, respectively. Additionally, the utmost amount of total carotenoid (614.18 mg100g−1 FW), β-carotene (0.47 mg/100 g FW), and ascorbic acid (84.61 mg g−1 FW) was obtained in C5. Ferulic acid (in C2 sample: Maragheh) and quercetin (in WA sample: Qaradag) were found to be the most abundant phenolic acid and flavonoid by HPLC–MS/MS analysis, respectively. No flavonoid of kaempferol was detected in the studied extracts from different regions. Wild and cultivated species in different regions were classified into four major clusters, according to hierarchical clustering analysis (HCA) method. Considering the cultivation of medicinal plants such as Physalis, the growing conditions must be carefully chosen because they affect the phytochemical components and especially the metabolism of polyphenols. Graphical Abstract